H1. Persistent maternal cardiac dysfunction after preeclampsia identifies patients at risk for recurrent pre-eclampsia. (12th August 2016) - Lo Presti, D.; Gagliardi, G.; Tiralongo, G. M.; Pisani, I.; Vasapollo, B.; Novelli, G. P.; Valensise, H.
Abstract: Objective : The purpose of our study was to assess cardiac function in non-pregnant women with previous early preeclampsia before a second pregnancy to highlight the cardiovascular pattern, which may take a risk for recurrent preeclampsia. Methods : Seventy-five normotensive patients with previous preeclampsia and 147 controls with a previous uneventful pregnancy were enrolled in a case control study and submitted to echocardiographic examination in the non-pregnant state 12–18 months after the first delivery. All patients included in the study had pregnancy within 24 months from the echocardiographic examination and were followed until term. Results : Twenty-two (29%) of the 75 patients developed recurrent preeclampsia. In the non-pregnant state, patients with recurrent preeclampsia compared to controls and non-recurrent preeclampsia had lower stroke volume (63 ± 14 mL versus 73 ± 12 mL and 70 ± 11 mL, p  < 0.05), cardiac output (4.6 ± 1.2 L versus 5.3 ± 0.9 L and 5.2 ± 1.0 L, p  < 0.05), higher E/E' ratio (11.02 ± 3.43 versus 7.34 ± 2.11 versus 9.03 ± 3.43, p  < 0.05), and higher total vascular resistance (1638 ± 261 dyne·s·cm −5 versus 1341 ± 270 dyne·s·cm −5 and 1383 ± 261 dyne·s·cm −5, p  < 0.05). Left ventricular mass index was higher in both recurrent and non-recurrent preeclampsia compared to controls (30.0 ± 6.3 g/m 2.7 and 30.4 ± 6.8 g/m 2.7 versus 24.8 ± 5.0 g/m 2.7, p  < 0.05). Conclusions : Signs of diastolic dysfunction and different left ventricular characteristics are present in the non-pregnant state before a second pregnancy with recurrent preeclampsia. Previous preeclamptic patients with non-recurrent preeclampsia show left ventricular structural and functional features intermediate with respect to controls and recurrent preeclampsia.